Digital enhancement and photogrammetric recording of La Joquera Levantine rock art (Borriol, Castelló) - Inés Domingo; Peyman Javadi; Dídac Roman (Virtual Archaeology Review)
The heritage values of Levantine rock art, as UNESCO World Heritage since 1998 and as an Asset of Cultural Interest since 1985 according to the Spanish Heritage Act, together with its fragile nature, demand developing initiatives aimed at regularly revisiting and monitoring the sites and updating any existing records (descriptions, tracings, photographs, etc.). This is especially important for long-known sites, such as La Joquera, discovered and first graphically recorded in 1930 and for which these records have not been updated for decades. Such revisits should be aimed to: a) asses the integrity of the finds since their discovery or since the last revision; b) test whether current digital technologies can improve previous interpretations and reproductions of the art preserved there; and c) produce accurate three-dimensional (3D) photorealistic models that capture the 3D nature of this heritage and even improve the visualisation of motifs. These integral approaches are relevant to the qualitative and quantitative study of the art, as well as to its preservation and monitoring, and creation of digital archives to ensure a virtual future for Levantine art. This paper reports the technologies and methods used, the challenges faced (in terms of space available, lighting restrictions and the visual interference caused by the protective fence), and the results obtained at La Joquera rock art site as part of the 2D and 3D digital recording of the rock surface, the colour and the motifs depicted. Highlights of this paper include the identification of previously invisible weaponry and adornments of the only archer preserved on this site, as well as some other incomplete remains. Deliverables also include the production of a photorealistic model on which colour-intensified tracings are projected. This facilitates the identification of art that is now extremely faded and offers a closer look at what the site may have looked like originally.